Pengkajian Agama Secara Historis - Tarigan, Mardinal; Aprila, Gusti; Pratama, Riswanda (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
As we know that history cannot be separated from a series of events that have been limited by space and time in which these events were formed and occurred. Many people say that history is something static that cannot possibly be